Tradisi Bhāākāl Ekakoãghĭ ( Perjodohan Sejak dalam Kandungan) di Desa Sana Laok, Kecamatan Waru, Pamekasan, Madura Dalam Perspektif Hukum Adat Dan Hukum Islam - Septi Karisyati Karisyati (UIN Sunan Kalijaga Yogyakarta, 2017)
The results showed that the village community asana Laok Waru District,Pamekasan, Madura is the majority of Muslims, more precisely NU Islam, classical.This marriage has existed since the time of their ancestors, is estimated to have existedabout 213 years ago and their obligation is only to preserve the cultural custom. Theysay that while it is not against the Islamic Shari'ah, there is no problem. Because thereis no Qur'anic proof that regulates it. The adat Bhakal Ekakoaghi does not contradictthe concept of an arranged marriage in Islam when it is greened from the purpose ofmatchmaking in accordance with maqasid al-syari'ah but there is little that is lessappropriate about its execution time when the child is still in the womb, such as buyinga cat in a sack, buying something uncertain. Besides that which is less in accordancewith Islamic law is about the legal consequences of the custom. In the custom there aremany legal consequences if it does not carry out the custom, while in Islam there is nolegal compromise from cancellation of an arranged marriage.